Disiplin Belajar Anak Berkebutuhan Khusus di SLB Panam Mulia Kecamatan Tampan Kota Pekanbaru - Nada Monika; Said Suhil Achmad; Daeng Ayub (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
This study is held back by the discipline of learning on special welfare children, so researchers want to study and formulate the problem vaitu studied how the discipline of the study of special needs children The study Uses a qualitative approach using a descriptive method, in this study its instrument is a person ora human instrument, that the researcher's sending data collection techniques in the study Interviews and documentaries based on data analysis and research findings on the discipline of the study of special-needs children in the new panam district, and asa result, the discipline of the learn of special-needs children in the New York City has been received. The rules, and the discipline used by a democratic type, as children need guidance and direction by teachers, and parental attention.